The Effectiveness of the Leadership of the Head of Service in Improving Employee Work Discipline - Kasiami, Sri; Wulandari, Septi; Hernanda, Ellena Putri; Saputri, Novita Elisa Rusdiana (Publik : (Jurnal Ilmu Administrasi), 2025)
This study aims to analyze the effectiveness of the leadership of the Head of Service in improving the work discipline of employees at the Bojonegoro Regency Library and Archives Service. The focus of this research is using theory of organizational effectiveness, which measures organizational effectiveness through three main dimensions: goal achievement, integration, and adaptation. The research method used is qualitative descriptive with data collection through interviews, observations, and documentation. The results of the study show that the leadership of the Head of Service has been effective in improving employee work discipline, as evidenced by the high level of employee attendance which is influenced by the fingerprint-based attendance system and reward and punishment mechanisms. Regular meetings between leaders and employees also play an important role in improving communication and cooperation. However, technical challenges, such as disruptions to facilities, as well as limited facilities and infrastructure, remain obstacles. In conclusion, good leadership, integration between teams, and adaptation to technological changes as well as strengthening facilities and infrastructure are the main factors in improving employee work discipline. Further research can explore further solutions to address infrastructure challenges and improve employee motivation..